2016
DOI: 10.1093/rpd/ncw135
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Scatter Radiation to Staff During Ct-Fluoroscopy: Monte Carlo Studies

Abstract: Studies have shown that there is high radiation exposure to medical staff during computed tomography fluoroscopy (CTF)-guided procedures. This study aims to investigate staff dose reduction techniques considering the CTF gantry positioning in the room and room dimensions in addition to the conventional use of thyroid collars, aprons and eye goggles. A Toshiba Aquilion One 640 slice CT scanner and CTF room were modelled using SimpleGeo. Standing and supine adult mesh phantoms were used to represent the staff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…CT has become commonly used in recent years for "treatment" purposes, such as tissue biopsy and drainage. Several reports have examined occupational dose to the lens of the eye in physicians performing these procedures [15,16,17,18,19,20,21,22,23] (Table 1), and special protective equipment and their effects in dose reduction [22,24,25,26]. However, while reports have already investigated nurses assisting pediatric patients in the CT room during CT scans for "diagnostic" purposes [27] or in phantom experiments [28,29], no reports have described direct measurement in medical staff assisting adult patients undergoing high-dose imaging procedures.…”
Section: Introductionmentioning
confidence: 99%
“…CT has become commonly used in recent years for "treatment" purposes, such as tissue biopsy and drainage. Several reports have examined occupational dose to the lens of the eye in physicians performing these procedures [15,16,17,18,19,20,21,22,23] (Table 1), and special protective equipment and their effects in dose reduction [22,24,25,26]. However, while reports have already investigated nurses assisting pediatric patients in the CT room during CT scans for "diagnostic" purposes [27] or in phantom experiments [28,29], no reports have described direct measurement in medical staff assisting adult patients undergoing high-dose imaging procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pediatric patients and those with frequent body movement may be assisted during routine outpatient CT examinations. Several studies reported on surgeon's lens exposure during CT fluoroscopy and interventional radiology (IR) [6][7][8][9][10][11][12][13][14][15]. Moreover, Suzuki et al determined the occupational dose to the eye lens of the CT-assisting radiologic technologists (RTs) using optically stimulated luminescence (OSL) dosimeters [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, reports on the exposure assessment and radiation protection of medical staff at the time of assistance of CT imaging were less than those for CT fluoroscopy (Suzuki et al 1997, 2001, Iida et al 2002, Tomita and Morozumi 2004, Neeman et al 2006, Heusch et al 2014, Nils et al 2015, Gyekye et al 2016, Fabian et al 2020, Siru et al 2021. During CT scans in the emergency department, medical staff are exposed scattered radiation by assisting CT examinations for various reasons, such as head holding, ventilation, and body movement suppression.…”
Section: Introductionmentioning
confidence: 99%